2022
DOI: 10.3389/fmars.2022.857594
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Water Export at the Brazil-Malvinas Confluence Evidenced From Combined in situ and Satellite Observations

Abstract: The Brazil-Malvinas Confluence (BMC) is the region where opposing and intense western boundary currents meet along the Southwestern Atlantic slope at about 38°S, generating one of the most energetic mesoscale regions of the global ocean. Based on shipborne observations acquired within the Uruguayan Economic Exclusive Zone (EEZ), combined with satellite data and an eddy tracking algorithm, we analyze the cross-shelf exchanges during May 2016, when the BMC was in an anomalous northern position. Two types of shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Maximum correlation with altimetry was not found in the upper layers where ageostrophic currents are considerable, but below 100 m depth, as observed in other regions (e.g. Manta et al, 2022). As a consequence of the altimetric detection of the Loop Current, a resulting limitation of this analysis is that the potential contribution of the higher frequencies (e.g.…”
Section: Discussionmentioning
confidence: 65%
“…Maximum correlation with altimetry was not found in the upper layers where ageostrophic currents are considerable, but below 100 m depth, as observed in other regions (e.g. Manta et al, 2022). As a consequence of the altimetric detection of the Loop Current, a resulting limitation of this analysis is that the potential contribution of the higher frequencies (e.g.…”
Section: Discussionmentioning
confidence: 65%
“…Prior studies have also shown that Brazil Current meanders (da Silveira et al., 2008) and eddies play an important role in cross‐shelf exchange in the northern region of Cape São Tome (22°S) (Calado et al., 2010; Palóczy et al., 2014). In the southern region where the Brazil Current collides with the Malvinas Current, offshore eddies are found to play a key role also in the location of the detrainment of the shelfwater to the deep ocean (Manta et al., 2022). Quantitative estimations of the magnitude of those cross‐shelf exchanges have been entirely based on model simulations (Berden et al., 2022; Combes & Matano, 2014; Matano et al., 2010; Palma et al., 2008; Palma & Matano, 2009).…”
Section: Introductionmentioning
confidence: 99%